2016
DOI: 10.1186/s12985-016-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

First identification of mammalian orthoreovirus type 3 in diarrheic pigs in Europe

Abstract: Mammalian Orthoreoviruses 3 (MRV3) have been described in diarrheic pigs from USA and Asia. We firstly detected MRV3 in Europe (Italy) in piglets showing severe diarrhea associated with Porcine Epidemic Diarrhea. The virus was phylogenetically related to European reoviruses of human and bat origin and to US and Chinese pig MRV3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…S1). It's noted that the porcine MRV reported recently in the USA and Europe (Lelli et al, 2016; Thimmasandra Narayanappa et al,…”
Section: Mrv-zj2013 Is Likely a Reassortant Mrv3 Strainmentioning
confidence: 98%
“…S1). It's noted that the porcine MRV reported recently in the USA and Europe (Lelli et al, 2016; Thimmasandra Narayanappa et al,…”
Section: Mrv-zj2013 Is Likely a Reassortant Mrv3 Strainmentioning
confidence: 98%
“…To define the MRV-3 infection in more detail, we combined sequencing reads from all time points and reconstructed a consensus sequence that covered the full coding sequences in all 10 segments of the MRV-3 isolate (GenBank KX932029 - KX932038). Phylogenetic analyses showed that the MRV-3 sequence isolated in this study was most related in all 10 segments to an isolate from a child in Slovenia [ 5 ] and further clustered with isolates from bats in Germany [ 6 ] and pigs in Italy [ 7 ] (Fig. 1a and Additional file 1 : Figures S1-S9).…”
Section: Case Presentationmentioning
confidence: 81%
“…The most unexpected finding was the infection with MRV-3, proven by metagenomic sequencing and serology of samples from several time points. MRVs belong to the Reoviridae family, a group of non-enveloped dsRNA viruses with 10 genome segments and have been isolated from a wide range of mammalian hosts and in a variety of clinical contexts [ 5 7 ]. To date, the diseases associated with MRV infections in humans include respiratory disease [ 8 ], meningitis [ 9 – 11 ], acute necrotizing encephalopathy [ 12 ] and (in a similar case involving a child living in Slovenia) acute gastroenteritis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among African countries, only two MRVs have been reported in Cameroon: a T4N strain, a prototype of serotype 4, isolated from a rodent [11,30,31]; and the CMR-HP55 strain detected from children with diarrhea [27]. Although MRVs isolated from pigs have been reported in Japan, China, South Korea, Italy and the USA [2,3,18,[32][33][34][35], they have never been detected from pigs in Africa. Understanding the distribution of MRV in Africa is important for veterinary and public health perspectives.…”
Section: Introductionmentioning
confidence: 99%